La agroindustria procesadora de cereales de Colombia, factores internos y externos inductores de cambio (2020)
This research compares the development of milling industries of wheat, corn and rice, in Colombia, from historical, economic, political and social points of view, since late XIX century until 2019. It analyses the influence of government decisions in industries and agricultural production, such as guarantee prices, customs taxes, in the same way as possible medium and longterm effects of agricultural associations and guilds. Among these effects are rent seeking and long-term lack of interest in building competitive capacity to confront other international producers. It emphasizes the benefits that guilds and similar entities might get from detected opportunities derived from public international institutions of agricultural research, such as IRRI in Philippines, CIAT in Colombia, and CYMMYT in Mexico. Related Latin American and world context is analyzed with some detail from an institutional point of view. Likewise, it is evaluated the incidence of changing exporting commercial trends, and new ideas of international agricultural supporting institutions as the USA PL 480 or free trade policies promoted by Thatcher and Reagan on the eighties. Moreover, some comparisons are made to highlight differences or similarities with other LatinAmerican countries. Additionally, benefits received by population are underlined when the country develops an efficient and competitive agriculture and industry.